A hydrophobic nanorod catalyst and its preparation method and application

By building a hydrophobic environment on the catalyst, using the nanorod-shaped solid solution oxide core and hydrophobic silicon oxide outer layer, the problem of by-product water when synthesis of dimethyl carbonate with carbon dioxide and methanol is solved, and the yield and catalyst activity of DMC are significantly improved. .

CN115999637BActive Publication Date: 2024-12-20DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211581897.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-09
Publication Date
2024-12-20
Estimated Expiration
2042-12-09

AI Technical Summary

Technical Problem

In the prior art, the reaction of carbon dioxide and methanol to synthesize dimethyl carbonate directly is affected by the by-product water, resulting in low DMC yield, and the catalyst surfactant sites are shielded by hydrolysis ions, the activation rate decreases, and the product yield is not high.

Method used

Using a hydrophobic nanorod catalyst composed of a nanorod-shaped solid solution oxide core and a hydrophobic-modified silicon oxide outer layer, the hydrophobic organic functional groups are grafted through a silane coupling agent to build a hydrophobic environment, promote the removal of water and the regeneration of active sites, and promote the The reaction equilibrium is towards the product generation direction.

Benefits of technology

The yield of dimethyl carbonate is significantly improved, the catalyst surface hydrophobic characteristics are excellent, the by-product water is repelled, the active site is regenerated, the reaction equilibrium is accelerated, and the selectivity and yield of DMC are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The present application discloses a hydrophobic nanorod catalyst and its preparation method and application. The catalyst comprises a metal oxide core and a silicon oxide outer layer, wherein the silicon oxide outer layer is coated on the surface of the metal oxide core; the metal oxide core is in the shape of a nanorod; the silicon oxide outer layer is hydrophobically modified; the metal oxide core is a solid solution oxide containing metal elements; the metal elements are selected from at least two of Ce, Fe, Co, Cu, Ni, Cr, and Zn. Through the uniform coating of the hydrophobically modified silicon oxide layer, the original strong hydrophilic property of the metal oxide surface is successfully reversed, and the desorption of hydrophilic species on the catalyst surface is accelerated. When applied to the direct synthesis of dimethyl carbonate from methanol and carbon dioxide, the removal of byproduct water on the catalyst surface is accelerated by virtue of the construction of the peripheral hydrophobic environment, which drives the generation of dimethyl carbonate from the perspective of reaction equilibrium and significantly improves the yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a hydrophobic nanorod catalyst and a preparation method and application thereof, belonging to the field of catalyst preparation. Background Art

[0002] Carbon dioxide (CO2), as an economical and renewable carbon source, has become an important research direction in C1 chemistry for its resource utilization to synthesize various chemicals and fuels.

[0003] Dimethyl carbonate (DMC) is an important organic chemical intermediate with the characteristics of non-toxic, non-corrosive, and biodegradable. Because its molecular structure contains groups such as -CH3, -OCH3, -CO-, and -COOCH3, and its chemical properties are active, it can be widely used in organic synthesis reactions such as methylation, methoxylation, carbonylation, and transesterification. In addition, with its excellent physical properties, DMC can be used as a new solvent, a new gasoline additive, and a lithium battery electrolyte. Due to its wide range of uses, DMC is also known as a "new building block" for organic synthesis in the 21st century.

[0004] Using carbon dioxide and methanol as raw materials, the direct synthesis of dimethyl carbonate by alcohol carboxylation reaction is a new green synthesis route of DMC that has attracted much attention in recent years. The reaction system has a wide source of raw materials, low cost, high atomic utilization rate of the reaction, and only produces water as a by-product, which meets the requirements of high atomic economy of green chemistry and non-toxicity of reactants and products. It has important theoretical and practical significance from the perspective of environmental protection and resource recycling. However, it is limited by the high thermodynamic stability and kinetic inertness of the substrate CO2 molecule and the severe thermodynamic equilibrium limitation of the reaction itself ( ), the yield of DMC is still very low, which limits its industrial application. The presence of byproduct water in the reaction system is an important factor that makes it difficult to improve the yield of DMC. The presence of water not only induces the reverse hydrolysis of DMC, but more seriously, the hydrogen ions and hydroxide ions formed by the dissociation of water will firmly bind to the active sites on the catalyst surface, shielding the active sites, resulting in a decrease in the activation rate of the substrate and a low product yield. Summary of the invention

[0005] In view of the problems existing in the prior art, the purpose of the present application is to provide a hydrophobic nanorod catalyst and a preparation method thereof and application in the synthesis of dimethyl carbonate. The catalyst is composed of a nanorod-shaped solid solution oxide inner core and a hydrophobically modified silicon oxide outer layer. Under the premise of ensuring that the active sites on the outer surface of the oxide are not excessively covered, the hydrophobic organic functional groups in the silane coupling agent are grafted and modified to successfully construct a hydrophobic environment on the periphery of the oxide, thereby accelerating the removal of byproduct water on the active sites in the direct synthesis of dimethyl carbonate from methanol and carbon dioxide, promoting the regeneration of the active sites while also pushing the reaction equilibrium towards the direction of product formation, thereby achieving a significant increase in the DMC yield.

[0006] According to one aspect of the present application, a hydrophobic nanorod catalyst is provided, comprising a metal oxide core and a silicon oxide outer layer, wherein the silicon oxide outer layer is coated on the surface of the metal oxide core;

[0007] The metal oxide core is in the shape of a nanorod;

[0008] The outer layer of silicon oxide is hydrophobically modified;

[0009] The metal oxide core is a solid solution oxide containing a metal element;

[0010] The metal elements are selected from at least two of Ce, Fe, Co, Cu, Ni, Cr, and Zn.

[0011] Optionally, the mass percentage of the oxide inner core in the catalyst is 42.6-78.8%, and the mass percentage of the silicon oxide outer layer in the catalyst is 21.2-57.4%.

[0012] Optionally, the silicon oxide outer layer is modified with a silane coupling agent containing a hydrophobic organic functional group.

[0013] Optionally, the silane coupling agent is selected from at least one of methyltriethoxysilane, n-propyltriethoxysilane, isobutyltriethoxysilane, n-hexyltriethoxysilane, n-octyltriethoxysilane, phenyltriethoxysilane, benzyltriethoxysilane, trimethylchlorosilane and hexamethyldisilazane.

[0014] According to another aspect of the present application, a method for preparing a hydrophobic nanorod catalyst is provided, comprising the following steps:

[0015] Step 1: mixing a precursor aqueous solution containing a metal element with a sodium hydroxide solution, crystallizing, and calcining to obtain a nanorod-shaped solid solution oxide containing the metal element;

[0016] Step 2: dispersing the solid solution oxide containing the metal element in an ethanol solvent, adding ethyl orthosilicate and ammonia water, reacting, collecting the solid product and drying it to obtain a silicon oxide-coated solid solution oxide;

[0017] Step 3: dispersing the silicon oxide-coated solid solution oxide in n-hexane, adding a silane coupling agent, heating, and drying II to obtain a hydrophobic nanorod catalyst;

[0018] The silane coupling agent contains a hydrophobic organic group.

[0019] Optionally, the concentration of the aqueous precursor solution containing metal elements is 0.1 to 0.4 mol / L, measured in moles of metal ions;

[0020] The concentration of the sodium hydroxide solution is 6.0-7.0 mol / L, measured in terms of hydroxide ion moles;

[0021] The molar ratio of the aqueous solution of the metal element precursor to the sodium hydroxide solution is 1:15-70.

[0022] Optionally, the concentration of the aqueous precursor solution containing metal elements is any value of 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, or a range between two values.

[0023] Optionally, the concentration of the sodium hydroxide solution is any value of 6.0 mol / L, 6.25 mol / L, 6.5 mol / L, 6.75 mol / L, 7.0 mol / L, or a range value between two values.

[0024] Optionally, the molar ratio of the aqueous solution of the metal element precursor to the sodium hydroxide solution is any value of 1:15, 1:30, 1:45, 1:60, 1:70, or a range between two values.

[0025] Optionally, the precursor aqueous solution containing metal elements is selected from a nitrate aqueous solution containing metal elements, and the metal elements are selected from at least two of Ce, Fe, Co, Cu, Ni, Cr, and Zn.

[0026] Optionally, the silane coupling agent is selected from at least one of methyltriethoxysilane, n-propyltriethoxysilane, isobutyltriethoxysilane, n-hexyltriethoxysilane, n-octyltriethoxysilane, phenyltriethoxysilane, benzyltriethoxysilane, trimethylchlorosilane and hexamethyldisilazane.

[0027] Optionally, in step 1, the crystallization temperature is 100-160° C., and the crystallization time is 24-32 hours.

[0028] Optionally, in step 1, the crystallization temperature is selected from any value of 100° C., 120° C., 140° C., 160° C., or a range between two values.

[0029] Optionally, the crystallization time is selected from any value among 24h, 28h, 30h, 32h, or a range between two values.

[0030] Optionally, the calcination temperature is 500-700° C., and the calcination time is 4-6 hours.

[0031] Optionally, the calcination temperature is any value of 500°C, 550°C, 600°C, 650°C, 700°C, or a range between two values.

[0032] Optionally, the calcination time is any value among 4h, 5h, 6h, or a range between two values.

[0033] Optionally, in step 2, the reaction time is 6 to 10 hours.

[0034] Optionally, in step 2, the reaction time is any value among 6h, 7h, 8h, 9h, 10h, or a range value between two values.

[0035] Optionally, the temperature of the drying I is 80-120° C., and the time of the drying I is 12-24 hours.

[0036] Optionally, the drying temperature I is any value among 80°C, 90°C, 100°C, 110°C, 120°C, or a range between two values.

[0037] Optionally, the drying time I is any value among 12h, 16h, 20h, 24h, or a range value between two values.

[0038] Optionally, in step 3, the heating temperature is 100-140° C., and the heating time is 8-12 h.

[0039] Optionally, in step 3, the heating temperature is any value of 100°C, 110°C, 120°C, 130°C, 140°C, or a range between two values.

[0040] Optionally, the heating time is any value among 8h, 9h, 10h, 11h, 12h, or a range value between two values.

[0041] Optionally, the temperature of the drying II is 60-100° C., and the time of the drying II is 18-24 hours.

[0042] Optionally, the drying temperature II is any value of 60°C, 70°C, 80°C, 90°C, 100°C, or a range between two values.

[0043] Optionally, the drying time II is any value among 18h, 20h, 22h, 24h, or a range value between two values.

[0044] According to another aspect of the present application, a method for preparing dimethyl carbonate is provided, wherein carbon dioxide is introduced into a reaction kettle containing a catalyst and methane, and reaction I is performed to obtain dimethyl carbonate;

[0045] The catalyst is selected from the above catalyst or the catalyst obtained according to the above preparation method.

[0046] Optionally, the catalyst accounts for 0.8-8.0 wt% of the methanol mass.

[0047] Optionally, the catalyst accounts for any value of 0.8wt%, 2wt%, 4wt%, 6wt%, 8wt% of the methanol mass, or a range between two values.

[0048] Optionally, the pressure in the closed container after adding carbon dioxide is 1~5Mpa.

[0049] Optionally, the pressure in the sealed container after adding carbon dioxide is any value among 1 Mpa, 2 Mpa, 3 Mpa, 4 Mpa, 5 Mpa, or a range between two values.

[0050] Optionally, the temperature of the reaction I is 100-140° C., and the temperature of the reaction I is 1-10 h.

[0051] Optionally, the temperature of the reaction I is selected from any value of 100°C, 110°C, 120°C, 130°C, 140°C, or a range between two values.

[0052] Optionally, the reaction time I is selected from any value among 1h, 3h, 5h, 7h, 10h, or a range between two values.

[0053] The beneficial effects of this application include:

[0054] 1) The hydrophobic nanorod catalyst provided in the present application has excellent surface hydrophobic properties. Without affecting the nanorod morphology of the solid solution oxide core, the original strong hydrophilic properties of the metal oxide surface are successfully reversed through the uniform coating of the silicon oxide layer and the grafting modification of the hydrophobic organic functional groups in the silane coupling agent, thereby accelerating the desorption of hydrophilic species on the catalyst surface.

[0055] 2) The preparation method of the catalyst provided in the present application is simple and efficient, the raw materials used for synthesis are cheap and easily available, the catalyst structure is stable and firm, and the hydrophobic silicon oxide layer is tightly combined with the metal oxide core and is not easy to fall off.

[0056] 3) The catalyst provided in the present application has excellent performance in the application of synthesizing dimethyl carbonate. By virtue of the construction of the outer hydrophobic environment, the water produced as a by-product of the reaction is repelled by the outer surface of the catalyst and is accelerated to leave the active sites of the catalyst, thereby promoting the regeneration of the active sites and pushing the reaction equilibrium toward the direction of product formation. Compared with the unmodified catalyst, the catalyst activity and DMC yield are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is an attenuated total reflection infrared spectrum of the hydrophobic nanorod catalyst prepared in Example 1 of the present application;

[0058] Figure 2 This is the attenuated total reflection infrared spectrum of the nanorod catalyst prepared in Comparative Example 2 of the present application;

[0059] Figure 3 This is a water drop contact angle diagram of the hydrophobic nanorod catalyst prepared in Example 1 of the present application;

[0060] Figure 4 This is a water drop contact angle diagram of the nanorod catalyst prepared in Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0061] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0062] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0063] The analysis method, conversion rate and selectivity in the embodiment are calculated as follows:

[0064] The qualitative and quantitative analysis of the products was performed offline using an Agilent 7890A gas chromatograph, with Agilent HP-PLOT Q and CP-WAX capillary columns used for separation and a hydrogen flame ionization detector (FID) for detection and analysis.

[0065] Methanol conversion rate = (total methanol mass - residual methanol mass) / total methanol mass * 100%

[0066] DMC selectivity = (number of moles of DMC*2) / number of moles of converted methanol*100%.

[0067] Example 1

[0068] Preparation of hydrophobic nanorod catalysts

[0069] (1) 0.10 g of copper nitrate trihydrate and 4.17 g of cerium nitrate hexahydrate were weighed and completely dissolved in deionized water at a molar ratio of n(Cu):n(Ce) = 0.04:0.96 to obtain a mixed metal salt solution A with a total metal ion concentration of 0.2 mol / L. 48 g of sodium hydroxide was completely dissolved in deionized water to obtain an alkaline solution B with a hydroxide concentration of 8.0 mol / L. The mixed metal salt solution A was quickly transferred to the alkaline solution B under stirring at room temperature and stirred for 30 min to obtain a suspension C. The suspension C was transferred to a stainless steel high-pressure synthesis autoclave lined with polytetrafluoroethylene, and the synthesis autoclave was placed in an oven at 120°C for crystallization for 30 h. The suspension obtained after the reaction was centrifuged, and the obtained solid product was alternately washed with deionized water and anhydrous ethanol, dried, and calcined at 650°C for 5 h to obtain a nanorod-shaped solid solution oxide core, recorded as Cu 0.04 Ce 0.96 O x -NR.

[0070] (2) 1.0 g Cu 0.04 Ce 0.96 O x -NR was ultrasonically dispersed in anhydrous ethanol, 3.0 mL of tetraethyl orthosilicate was added, and the mixture was stirred for 5 h, and then 10.0 mL of ammonia water was added, and the mixture was stirred for 5 h. The suspension obtained after the reaction was filtered and washed with ethanol, and the solid product was dried in a drying oven to obtain a silicon oxide-coated nanorod solid solution oxide, which was recorded as Cu 0.04 Ce 0.96 O x -NR-Si3.

[0071] (3) 1.0g Cu 0.04 Ce 0.96 O x -NR-Si3 was dispersed in 25.0 mL of n-hexane, 1.0 mL of methyltriethoxysilane was added, and the mixture was stirred and refluxed in a constant temperature oil bath at 120 °C for 10 h. The mixture was subsequently filtered, washed with n-hexane, and dried in a vacuum drying oven to obtain a hydrophobic nanorod catalyst, which was recorded as Cu 0.04 Ce 0.96 O x -NR-Si3-MTES1.

[0072] Figure 1 and Figure 2 Compared with the characterization results of the hydrophobic nanorod catalysts coated with silicon oxide and hydrophobically modified with silane coupling agent, the infrared peak intensity of the surface hydroxyl group and adsorbed water species was significantly reduced (3460cm -1 、1627cm -1 ), and infrared vibration peaks (1070cm-1) attributed to Si-O-Si stretching vibration and bending vibration appeared at the same time.-1 、802cm -1 、441cm -1 ) and the infrared vibration peak of CH (2967cm) attributed to the hydrophobic alkyl functional group in the silane coupling agent -1 ), the outer layer of silicon oxide and the hydrophobic groups effectively cover the surface of the metal oxide core.

[0073] Figure 3 and Figure 4 Comparison of characterization results shows that the water droplet contact angle on the surface of the hydrophobic nanorod catalyst after being coated with a silicon oxide outer layer and hydrophobically modified with a silane coupling agent increased from 8.2° to 80.2°, and the strong hydrophilicity of the original surface was effectively suppressed, which is beneficial to the rapid removal of by-product water on the catalyst surface.

[0074] Embodiments 2 to 20

[0075] Preparation of hydrophobic nanorod catalysts

[0076] Referring to the synthesis conditions and operation steps of Example 1, a series of hydrophobic nanorod catalysts were prepared by changing the type and amount of metal element precursor, the amount of tetraethyl orthosilicate, the type and amount of silane coupling agent, etc. The catalyst preparation conditions are shown in Table 1.

[0077] Table 1 Catalyst preparation conditions

[0078]

[0079] Comparative Example 1

[0080] Preparation of hydrophobic nanorod catalysts

[0081] The catalyst preparation method is the same as that of Cu in Example 1 0.04 Ce 0.96 O x -NR-Si3-MTES1 is prepared in the same manner, except that in step (1), only 4.34 g of cerium nitrate hexahydrate is weighed as the catalyst raw material, and the resulting catalyst is recorded as CeO2-NR-Si3-MTES1.

[0082] Comparative Example 2

[0083] Preparation of nanorod catalysts

[0084] The catalyst preparation method is similar to that of Cu in Example 7. 0.12 Ce 0.88 O x -NR-Si3-MTES1 is similar in preparation, except that the Cu obtained in step (1) 0.12 Ce 0.88 O x-NR was not subjected to the hydrophobic modification treatment of steps (2) and (3), and the resulting catalyst was recorded as Cu 0.12 Ce 0.88 O x -NR.

[0085] Embodiments 21 to 48

[0086] Application of hydrophobic nanorod catalyst in the synthesis of dimethyl carbonate

[0087] The synthesis evaluation of dimethyl carbonate was carried out in a 100mL autoclave: 500 mg of each catalyst prepared in Example 1, Example 2-20 and Comparative Example 1 and Comparative Example 2 were mixed with 15 g of methanol and added to the autoclave and sealed, and nitrogen was introduced to replace and purge the air in the autoclave, and repeated 3 times. After the air in the autoclave was replaced and exhausted, high-pressure CO2 gas was filled to the set pressure, and the heating and stirring switches were turned on. After the temperature in the autoclave rose to the target temperature, the start reaction time was recorded. After the reaction was completed, the reactor was taken out and rapidly cooled in an ice water bath. After cooling was completed, the pressure was slowly released and the autoclave was opened. The liquid product was quantitatively analyzed by internal standard method on an Agilent 7890A gas chromatograph equipped with a hydrogen flame ionization detector (FID) and a CP-WAX capillary column. The catalyst performance evaluation results are shown in Table 2.

[0088] Table 2 Performance evaluation of hydrophobic nanorod catalysts

[0089]

[0090] The hydrophobic nanorod catalyst prepared in the embodiment of the present invention has excellent catalytic performance when catalyzing methanol and carbon dioxide to directly synthesize dimethyl carbonate, and the DMC selectivity is close to 100% and the yield is high.

[0091] Comparing the results of Examples 21 to 26 with 47, the hydrophobic nanorod catalyst constructed with a solid solution oxide composed of bimetallic components as the core has better catalytic performance.

[0092] Comparison of the results of Examples 27 and 48 shows that the construction of the hydrophobic environment on the outer surface of the oxide promotes the rapid removal of byproduct water from the active sites on the catalyst surface, pushing the reaction equilibrium toward product formation. The DMC yield increased from 8.12 mmol g -1 Significantly increased to 12.79mmol g -1 .

[0093] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A hydrophobic nanorod catalyst, characterized in that: It comprises a metal oxide core and a silicon oxide outer layer, wherein the silicon oxide outer layer is coated on the surface of the metal oxide core; The metal oxide core is in the shape of a nanorod; The silicon oxide outer layer is modified by a silane coupling agent containing a hydrophobic organic functional group; The metal oxide core is a solid solution oxide containing a metal element; The metal element contains one of Fe, Co, Cu, Ni, Cr, Zn and Ce; The mass percentage of the metal oxide inner core in the catalyst is 42.6-78.8%, and the mass percentage of the silicon oxide outer layer in the catalyst is 21.2-57.4%; The silane coupling agent is selected from at least one of methyltriethoxysilane, n-propyltriethoxysilane, n-hexyltriethoxysilane, phenyltriethoxysilane, trimethylchlorosilane and hexamethyldisilazane; The hydrophobic nanorod catalyst is obtained by the following steps: Step 1: mixing a precursor aqueous solution containing a metal element with a sodium hydroxide solution, crystallizing, and calcining to obtain a nanorod-shaped solid solution oxide containing the metal element; Step 2: dispersing the solid solution oxide containing the metal element in an ethanol solvent, adding ethyl orthosilicate and ammonia water, reacting, collecting the solid product and drying it to obtain a silicon oxide-coated solid solution oxide; Step 3: Disperse the silicon oxide-coated solid solution oxide in n-hexane, add a silane coupling agent, heat, and dry II to obtain a hydrophobic nanorod catalyst.

2. The hydrophobic nanorod catalyst according to claim 1, characterized in that The concentration of the aqueous precursor solution containing metal elements is 0.1-0.4 mol / L, measured in terms of metal ion moles; The concentration of the sodium hydroxide solution is 6.0-7.0 mol / L, measured in terms of hydroxide ion moles; The molar ratio of the metal element-containing precursor aqueous solution to the sodium hydroxide solution is 1:15-70; The precursor aqueous solution containing metal elements is selected from a nitrate aqueous solution containing metal elements.

3. The hydrophobic nanorod catalyst according to claim 1, characterized in that The volume ratio of the solid solution oxide containing metal elements to tetraethyl orthosilicate, ammonia water and ethanol is 1 g: 1 mL to 5 mL: 10 mL to 15 mL: 40 mL to 60 mL; The volume ratio of the mass of the silicon oxide-coated solid solution oxide to n-hexane and the silane coupling agent is 1 g: 10 mL to 25 mL: 0.5 mL to 3 mL.

4. The hydrophobic nanorod catalyst according to claim 1, characterized in that In step 1, the crystallization temperature is 100-160° C., and the crystallization time is 24-32 hours; The calcination temperature is 500-700°C, and the calcination time is 4-6h; In step 2, the reaction time is 6 to 10 hours; The temperature of the drying I is 80-120° C., and the time of the drying I is 12-24 hours.

5. The hydrophobic nanorod catalyst according to claim 1, characterized in that In step 3, the heating temperature is 100-140° C., and the heating time is 8-12 hours; The temperature of the drying II is 60-100° C., and the time of the drying II is 18-24 hours.

6. A method for preparing dimethyl carbonate, characterized in that: Introducing carbon dioxide into a sealed container containing a catalyst and methanol to perform reaction I to obtain dimethyl carbonate; The catalyst is selected from the hydrophobic nanorod catalyst according to any one of claims 1 to 5.

7. The preparation method according to claim 6, characterized in that: The catalyst accounts for 0.8-8.0wt% of the methanol mass; The pressure in the sealed container after the carbon dioxide is introduced is 1-5 MPa; The temperature of the reaction I is 100-140° C., and the time of the reaction I is 1-10 h.